Colissepticemia neonatal em um canino – RELATO DE CASO - Alberti, Taina dos Santos; Bonel, Josiane; Venancio, Fabiano da Rosa; da Rosa, Cristiano Silva; Ladeira, Silvia Leal; Pereira, Daniela Isabel Brayer (Brazilian Journal of Veterinary Medicine, 2019)
Escherichia coli is a Gram-negative bacterium, belonging to commensal microbiota of the gastrointestinal tract of animals and humans. Some strains have virulence factors, which may cause enteritis and / or septicemia. In the septicemic form of the disease, the main predisposing factor is not ingestion or ingestion of insufficient amounts of colostrum. The objective of this study is to report a case of neonatal colissepticemia in a five-day-old canine. At necropsy of the corpse, congestion was observed in organs of the abdominal and thoracic cavities, and multifocal whitish areas with coalescents in the kidneys and lungs. Histopathological examination of the kidney, liver, lung and heart showed multifocal areas of necrosis with presence of myriad intralesional bacteria. In the organ samples sent to the microbiological diagnosis there was growth of E. coli. The clinical history, as well as the histopathological and microbiological findings allow us to infer that the cause of death was due to a sepsis caused by E. coli.